Pengaruh Hubungankemampuan Komunikasi dan Penalaran Matematika Siswa Kelas VIII Terhadap Hasil Belajar Yang Diajar Dengan Model Pembelajaran Group Investigation (GI) - Imanuel Munthe; Waminton Rajagukguk (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to determine whether there is a positive and significant effect of the Group Investigation type cooperative learning model on students' mathematical reasoning and communication skills in the Pythagorean Theorem sub-subject in class VIII SMP Negeri 1 Munte in the 2019/2020 Academic Year. The population in this study were all class VIII students of SMP Negeri 1Munte for the 2019/2020 Academic Year. While the sample in this study consisted of 2 classes of 38 students each in class VIII-1 as the experimental class and class VIII-3 as the control class. The experimental class uses the Group Investigation cooperative learning model consisting of 5 students per group, and the control class uses the Group Investigation type cooperative learning model consisting of 2 students per group. This type of research is an experiment. Prior to testing the hypothesis, the normality and homogeneity tests are tested first. Normality was tested using the Lilliefors technique and homogeneity using the F test. From the tests performed, it was found that both samples were normally distributed and homogeneous. There is a positive and significant influence of the Group Investigation cooperative learning model on the mathematical reasoning abilities of junior high school students. There is a positive and significant influence of the Group Investigation type of cooperative learning model on the mathematical communication skills of junior high school students because the average communication ability of students who are taught with the Group Investigation type cooperative learning model consisting of 5 people per group is higher than the average communication ability of students who are taught with the Group Investigation type cooperative learning model consisting of 2 people per group